BAZNAS Kabupaten Maros: Optimalisasi Pengelolaan Zakat Sebagai Sarana Meningkatkan Kesejahteraan Masyarakat : BAZNAS Maros Regency: Optimizing Zakat Management as a Means of Improving Community Welfare - Atika, Nur; Zahratul Mawaddah (ISTIDLAL, 2024)
This research aims to examine the optimization of zakat management as a means of improving community welfare, by referring to Law of the Republic of Indonesia Number 23 of 2011 concerning Zakat Management and Law Number 11 of 2009 concerning Social Welfare. The focus of the research is the strategy implemented by BAZNAS Maros Regency in maximizing the potential of zakat and the effectiveness of its distribution in improving community welfare. This study uses a qualitative descriptive method with a field research approach, using primary data from the Maros Regency BAZNAS office and secondary data in the form of related legal materials. The results of the study show that the strategy of BAZNAS Maros Regency includes zakat publications to increase public awareness, transparent administrative management, and real action in distribution and empowerment. The effectiveness of zakat distribution is influenced by the potential of community zakat, the amount of zakat funds that have been successfully collected, and the success of the distribution program despite facing obstacles in the collection and utilization of zakat. Scientifically, this research is expected to be a reference in the development of zakat management science and contribute to the scientific community, students, and related parties in an effort to improve the welfare of the community, nation, and religion.